Hepatitis C virus infects rhesus macaque hepatocytes and simianized mice. Issue 1 (15th April 2015) - Scull, Margaret A.; Shi, Chao; de Jong, Ype P.; Gerold, Gisa; Ries, Moritz; von Schaewen, Markus; Donovan, Bridget M.; Labitt, Rachael N.; Horwitz, Joshua A.; Gaska, Jenna M.; Hrebikova, Gabriela; Xiao, Jing W.; et al.
Abstract : At least 170 million people are chronically infected with hepatitis C virus (HCV). Owing to the narrow host range of HCV and restricted use of chimpanzees, there is currently no suitable animal model for HCV pathogenesis studies or the development of a HCV vaccine. To identify cellular determinants of interspecies transmission and establish a novel immunocompetent model system, we examined the ability of HCV to infect hepatocytes from a small nonhuman primate, the rhesus macaque ( Macaca mulatta ). We show that the rhesus orthologs of critical HCV entry factors support viral glycoprotein‐dependent virion uptake. Primary hepatocytes from rhesus macaques are also permissive for HCV‐RNA replication and particle production, which is enhanced when antiviral signaling is suppressed. We demonstrate that this may be owing to the diminished capacity of HCV to antagonize mitochondrial antiviral‐signaling protein–dependent innate cellular defenses. To test the ability of HCV to establish persistent replication in vivo, we engrafted primary rhesus macaque hepatocytes into immunocompromised xenorecipients. Inoculation of resulting simian liver chimeric mice with either HCV genotype 1a or 2a resulted in HCV serum viremia for up to 10 weeks. Conclusion : Together, these data indicate that rhesus macaques may be a viable model for HCV and implicate host immunity as a potential species‐specific barrier to HCV infection. We conclude that suppression of host immunity or further viral adaptation may allow robust HCV infection in rhesus macaques and creation of a new animal model for studies of HCV pathogenesis, lentivirus coinfection, and vaccine development. (Hepatology 2015;62:57‐67)